1996
DOI: 10.1136/thx.51.10.985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrostatic charge, flow, delay and multiple actuations on the in vitro delivery of salbutamol from different small volume spacers for infants.

Abstract: Background -A study was undertaken to determine the influences of electrostatic charge, flow, delay, and multiple actuations on the in vitro delivery of salbutamol generated by a pressurised metered dose inhaler (pMDI) from small volume spacers used in infants. Methods -Ten actuations from a salbutamol pMDI were drawn at different flow rates after either single or multiple actuations, with or without delay, through either static or reduced static spacers. An ionic detergent was used to reduce the charge of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
1
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 12 publications
3
96
1
4
Order By: Relevance
“…The in vitro studies confirm and extend the authors' previous work [8,10]. Coating a plastic spacer with an ionic detergent is a simple method of reducing electrostatic charge, thereby increasing the in vitro drug delivery.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The in vitro studies confirm and extend the authors' previous work [8,10]. Coating a plastic spacer with an ionic detergent is a simple method of reducing electrostatic charge, thereby increasing the in vitro drug delivery.…”
Section: Discussionsupporting
confidence: 87%
“…However, the authors' previous in vitro work [8,10] has demonstrated that detergent coating improves the delivery of salbutamol through different plastic spacers (Aerochamber1, Babyhaler1, Babyspacer1, Nebuhaler1, and Volumatic), confirming that electrostatic charge plays a major role. A low-volume metal spacer [21] has been developed to eliminate the problem of static charge, but in view of the present results and the issues of cost and availability, a simple plastic spacer may remain the device of choice worldwide.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Проблема синхронизации вдоха с моментом посту-пления лекарственного препарата -одна из самых важных при использовании дозированных аэрозольных ингаляторов. Не все дети оказываются в состоянии пра-вильно освоить этот дыхательный маневр, поэтому для оптимизации осаждения медикамента применяют рас-пределяющее устройство -спейсер [35].…”
Section: муколитическая терапияunclassified
“…Fakat basit ve pratik bir yöntem olan aracı tüpün yüzeyini gün-de bir iyonik deterjan ile kaplamanın akciğere ulaşan ilaç miktarını %50-70 oranında artırdığı ve akciğere giden ilaç miktarının belirlenmesinde elektrostatik yükü ortadan kaldırmanın ilaç akım hızından daha önemli olduğu ortaya konmuştur. Ayrıca, yeni kullanılmaya baş-lanan tüplerin daha fazla elektrostatik yük içermesin-den dolayı kullanımda olan eski aracı tüplere göre hastaya ulaşan ilaç miktarında anlamlı bir azalmaya neden olduğu, aracı tüpü kullandıktan sonra sadece su ile yı-kamanın elektrostatik yükü azaltmadığı ve dolayısıyla hastaya ulaşan ilaç miktarını azalttığı, aracı tüpün iç yüzeyini alüminyum folyo ile kaplamanın iyonik deterjanla maruziyete benzer şekilde elektrostatik yükü anlamlı oranda azalttığı gösterilmiştir (12,13).…”
Section: Araci Tüpunclassified